KESANTUNAN BAHASA SMS (SHORT MESSAGE SERVICE) MAHASISWA TERHADAP DOSEN JURUSAN BAHASA INDONESIA PADA SEMESTER GANJIL 2017/2018 DI UNIVERSITAS MAHAPUTRA MUHAMMAD YAMIN SOLOK - Rahmi, Ulva; Tressyalina, Tressyalina; Noveria, Ena (Universitas Negeri Padang, 2018)
There are four aims of the reseaech. First, to decribe how is the way to communicate toward the lecture. Second, to describe the principle of languange politeness in sending SMS to the lecturer. Third, to describe the scale of students languange politeness in sending SMS. Fourth, to describe the politeness of student’s languange SMS toward lecturer. This reseaech used qualitative research which used descriptive methode. It was done at Universitas Mahaputra Muhammad Yamin Solok. It is important to be conducted because it could be the way how to explore the student’s languange politeness in daily life. The instrument of this research is the reseracher herself which has collected the data for one semester 2017/2018. Kata kunci: Kesantunan, etika, prinsip kesantunan, skala kesantunan